Energy-saving control of multi-robot systems - Yang, Xiaoxuan (2015)
Multi-robot systems are getting more popular in the area of robotics. Multi-robot systems are more likely to accomplish complicated tasks while providing efficiency and reliability compared to a single robot. Conserving energy of the robots is also important so that the robots could accomplish more tasks with the constraint of the battery capacity. Research of robotics allow one to realise that some human functions can be applied to a robot. An example would be a person walking along a path. It is an involuntary reaction that a person aim to walk anywhere along the path as long as one stay on the path. It could be seen that the goal position is actually a region instead of a specific point. In addition, one would use his eyes to look for any incoming object to change his path direction to avoid collision. These could all be applied on the robots where the robots would run in a region and using sensors to avoid collision when running in a group. The robots are set to run with conventional trajectory and region trajectory. Conventional trajectory is a traditional method for the robot to the goal position by going to a specific point. Region trajectory control can be visualised as robot travelling within a defined playing field. The robot can travel anywhere within the defined region. The author also set different robot formation to run within the designated region. In order to for multi-robots to run in an orderly manner, a certain pattern need to be considered. In this project, it is required to find out if the robot formation is a factor for energy consumption. This project focus on power consumption of the robots. As the robots are battery-powered, energy measurements would be taken using a power analyser while running the trajectories. Energy consumption will be calculated with the current and voltage values from the power analyser. Energy comparison will be make for different robot formations for different trajectories. There are some constraints faced due to the nature of the robot and the software thus it is necessary to maximize the utility of the robot to meet the goals and also to save on power consumption.In conclusion, a multi-robot system is particularly useful for completing tasks without much supervision. More power-saving controllers could be researched and developed to allow robots to run for a longer time.